Global, regional, and national burden of spinal injuries attributable to road injuries: a systematic analysis of incidence, prevalence, and YLDs with projections to 2046 - Deng, Yanqing; Feng, Yansong; Ou, Xuancheng; Lan, Yanni; Wei, Jiyong; He, Qing (Frontiers in Public Health, 2025)
BackgroundRoad injuries remain a critical global public health issue, with spinal injuries representing a major contributor to long-term disability. This study systematically analyzes the global, regional, and national burden of spinal injuries attributable to road injuries from 1990 to 2021 and projects trends to 2046.MethodsUsing data from the Global Burden of Disease (GBD) 2021 study, we estimated incidence, prevalence, and years lived with disability (YLDs) for spinal injuries caused by road traffic, analyses spanned 204 countries, stratified by sex, age, and Socio-demographic Index (SDI) regions, GBD regions, and countries. Age-standardized rates (ASRs) per 100,000 population were calculated, and temporal trends (1990–2021) were assessed via estimated annual percentage change (EAPC). Future projections (2022–2046) utilized age-period-cohort (APC) modeling.ResultsIn 2021, road injuries caused 95,734 (95% UI: 66,597–138,308) incident spinal injuries globally, with 2.63 million (95% UI: 2.39–2.93 million) prevalent cases and 777,365 (95% UI: 552,847–1,004,818) YLDs. Males bore 2.9–2.7 times higher burden than females. Age-standardized incidence (ASIR), prevalence (ASPR), and YLDs rates (ASYLDR) peaked in the 65–69 age group (ASPR: 75.00/100,000; ASYLDR: 20.64/100,000). High SDI regions exhibited the highest ASRs (ASIR: 2.28/100,000; ASYLDR: 16.83/100,000), while Middle SDI regions had the largest absolute caseloads (incidence: 27,086; prevalence: 703,112). From 1990 to 2021, global ASIR declined by 40% (1.95–1.17/100,000) and ASYLDR by 46% (16.85–9.17/100,000). By 2046, male incidence is projected to rise by 5.3%, with ASYLDR remaining three-fold higher in males than females (10.86 vs. 3.61/100,000).ConclusionDespite declining age-standardized rates, the absolute burden of road injury-related spinal trauma persists, particularly in Middle SDI regions. Targeted interventions, enhanced road safety policies, gender-specific prevention programs, and improved trauma care, are critical to mitigate disparities. Projections underscore the urgent need for equitable strategies to address rising burdens in aging and rapidly motorizing populations.